Substandard and counterfeit medicines: a systematic review of the literature - Almuzaini, Tariq; Choonara, Imti; Sammons, Helen (BMJ Publishing Group, 2013)
Objective: To explore the evidence available of poorquality (counterfeit and substandard) medicines in the literature. Design: Systematic review. Data sources: Databases used were EMBASE, MEDLINE, PubMed and the International Pharmaceutical Abstracts, including articles published till January 2013. Eligibility criteria: Prevalence studies containing original data. WHO definitions (1992) used for counterfeit and substandard medicines. Study appraisal and synthesis: Two reviewers independently scored study methodology against recommendations from the MEDQUARG Checklist. Studies were classified according to the World Bank classification of countries by income. Data extraction: Data extracted: place of study; type of drugs sampled; sample size; percentage of substandard/counterfeit medicines; formulations included; origin of the drugs; chemical analysis and stated issues of counterfeit/substandard medicines. Results: 44 prevalence studies were identified, 15 had good methodological quality. They were conducted in 25 different countries; the majority were in low-income countries (11) and/or lower middle-income countries (10). The median prevalence of substandard/counterfeit medicines was 28.5% (range 11–48%). Only two studies differentiated between substandard and counterfeit medicines. Prevalence data were limited to antimicrobial drugs (all 15 studies). 13 studies involved antimalarials, 6 antibiotics and 2 other medications. The majority of studies (93%) contained samples with inadequate amounts of active ingredients. The prevalence of substandard/counterfeit antimicrobials was significantly higher when purchased from unlicensed outlets (p<0.000; 95% CI 0.21 to 0.32). No individual data about the prevalence in upper middle-income countries and high-income countries were available. Limitations: Studies with strong methodology were few. The majority did not differentiate between substandard and counterfeit medicines. Most studies assessed only a single therapeutic class of antimicrobials. Conclusions: The prevalence of poor-quality antimicrobial medicines is widespread throughout Africa and Asia in lower income countries and lower middle-income countries . The main problem identified was inadequate amounts of the active ingredients.